2015
DOI: 10.1016/j.bmhimx.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Transición parasitaria: experiencia en un hospital pediátrico de tercer nivel (1990-2010)

Abstract: Behavioral tendency of intestinal parasitosis during the last two decades shows a change in frequency and genera from the agents that were reported at this pediatric health care level. The processing of epidemiologic information is important in order to determine the response of the parasitosis and its variations over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
0
1
3
Order By: Relevance
“…With respect to the helminths, the prevalence of A. lumbricoides infection in this study was 5.8% (6/104), which is less than observations reported in the study of the general population of San Pedro Itzicán, which was 3 times higher (17.5%) than in San Juan Cosala [6]. The low prevalence of helminths found in San Juan Cosala could be, at least in part, the result of the massive deworming campaigns that have been implemented in Mexico [40]. Other studies have reported a decrease in the prevalence of this type of enteric parasite [41].…”
Section: Discussioncontrasting
confidence: 63%
“…With respect to the helminths, the prevalence of A. lumbricoides infection in this study was 5.8% (6/104), which is less than observations reported in the study of the general population of San Pedro Itzicán, which was 3 times higher (17.5%) than in San Juan Cosala [6]. The low prevalence of helminths found in San Juan Cosala could be, at least in part, the result of the massive deworming campaigns that have been implemented in Mexico [40]. Other studies have reported a decrease in the prevalence of this type of enteric parasite [41].…”
Section: Discussioncontrasting
confidence: 63%
“…En este estudio, la prevalencia de parasitosis en niños que son atendidos en guarderías fue de 19.1%, valor más bajo que los datos reportados previamente en otros estudios en la República mexicana, ya que varían de 37 a 100%. [9][10][11][12] Esta baja prevalencia podría explicarse por el Programa de Salud de las Guarderías, el cual promueve la revisión anual de parasitosis por medio de estudios de laboratorio. Esto es obligatorio Figura 1: Prevalencia de parasitosis de acuerdo con la edad.…”
Section: Discussionunclassified
“…19 Con respecto a los parásitos detectados, el protozoario Blastocystis hominis fue el más frecuente (43.8%), seguido del protozoario Endolimax nana en 20.3% y Giardia lamblia en 10.5%. En estudios previos en México las tasas varían de 4.0 a 62%, [8][9][10][11][12] donde Blastocystis hominis es el que también predomina. En 2008 este parásito alcanzó 90% 20 en el estado de Guerrero y ese mismo año en Teximalpa, Huayacocotla, Veracruz también se encontró una prevalencia de 80% en 100 niños de seis a 14 años.…”
Section: Wwwmedigraphicorgmxunclassified
See 1 more Smart Citation